FAO commodity review and outlook 1977-1979. - Food and Agriculture Organisation (Rome: Food and Agriculture Organisation of the United Nations, 1978)
The world agricultural commodity situation in 1977 and 1978 was charecterised by more abundant supply of most major commodities, rising world prices, and new record values of world trade.
lje 14/06/2017
Loans
Keywords: Agriculture--Economic aspects; Primary commodities; Agricultural industries; Produce trade; Commercial products